Kualitas Pelayanan Keperawatan di Rumah Sakit Umum Daerah (RSUD) Kota Baubau (Jurnal Kesehatan Manarang, 2020)
The enhancement of service quality, the availability of facilities, and the independence by the hospital as a national health subsystem. Thus, the hospital is required to provide high-quality health services that are managed by superior nursing resources to create efficiency, quality of service, in meeting patient needs. This research aims to analyze the quality of nursing services in Baubau City Regional General Hospital by using a qualitative method, where this research is a more descriptive and in-depth analysis and highlighting the perspective of the subjective. The theoretical basis used became a guide so that the focus of research in line with events in the field. The results showed the quality of service consisting of a) reliability that nurses were able to provide the promised service immediately and satisfactorily; b) Assurance where nurses had the knowledge, ability, hospitality, courtesy, and trustworthiness to eliminate consumer doubts; c) Tangible, the ability to provide tangible evidence of nursing services for patients; d) Empathy includes the nurse's capability in terms of excellent communication, attention, understanding the personal needs of patients; e) Responsiveness is the desire or willingness of nurses to help and provide nursing services to patients. Therefore, this research concludes that most of the informants felt happy and satisfied with nursing services, but for the Responsiveness dimension, many informants said they were not satisfied.